Minimax Control Problems: Optimality Conditions - Aquino, P. G.P. [UNESP]; De Pinho, M.D.R.; Silva, G. N. [UNESP] (Elsevier, 2021)
The formulation of the minimax control problem is considered. We allow for parameter uncertainties in all functions involved: in the cost function, in the dynamical control system and in the equality and inequality constraints. Weak maximal principle for minimax optimal control problems with mixed state-control equality and inequality constraints, under the constraint qualification of Mangassarian-Fromovitz type are discussed. The optimality conditions under a full rank conditions type is derived, and it is shown that it is, as usual, a particular case of the Mangassarian-Fromovitz type condition case. We also look at the necessary conditions of optimality for simplified versions of the model and degeneracy issues.
Keywords: maximum principle; minimax control; mixed constrained; optimal control problems